A high-resolution map of small-scale inversions in the gibbon genome - Mercuri, Ludovica; Palmisano, Donato; L'Abbate, Alberto; D'Addabbo, Pietro; Montinaro, Francesco; Catacchio, Claudia Rita; Hasenfeld, Patrick; Ventura, Mario; Korbel, Jan O.; Sanders, Ashley D.; Maggiolini, Flavia Angela Maria; Antonacci, Francesca (Genome Research, 2022)
Gibbons are the most speciose family of living apes, characterized by a diverse chromosome number and rapid rate of large-scale rearrangements. Here we performed single-cell template strand sequencing (Strand-seq), molecular cytogenetics, and deep in silico analysis of a southern white-cheeked gibbon genome, providing the first comprehensive map of 238 previously hidden small-scale inversions. We determined that more than half are gibbon specific, at least fivefold higher than shown for other primate lineage-specific inversions, with a significantly high number of small heterozygous inversions, suggesting that accelerated evolution of inversions may have played a role in the high sympatric diversity of gibbons. Although the precise mechanisms underlying these inversions are not yet understood, it is clear that segmental duplication–mediated NAHR only accounts for a small fraction of events. Several genomic features, including gene density and repeat (e.g., LINE-1) content, might render these regions more break-prone and susceptible to inversion formation. In the attempt to characterize interspecific variation between southern and northern white-cheeked gibbons, we identify several large assembly errors in the current GGSC Nleu3.0/nomLeu3 reference genome comprising more than 49 megabases of DNA. Finally, we provide a list of 182 candidate genes potentially involved in gibbon diversification and speciation.
10.1101/gr.276960.122